Magnetic characterisation using approximation method (APM) of BaFe12 0 19 derived from millscale / R. S. Azis … [et al.] - M., Hashim; N., Yahya; H., Azhan; R., Alias; N. M., Saiden; N. A., Aini; A. A., Rejab (Universiti Teknologi MARA Cawangan Pahang, 2005)
This paper describes a new method for measuring the magnetic properties of hexagonal Barium ferrite using approximation method (APM) theory. The sample was prepared by recycling the waste steel product from Malaysian steel factories. Using a Curie temperature separation technique, the wustite, FeO contained in the millscale was separated by this new technique using de-ionized water at 90°CI 100°C in the presence of IT external field. The wustite was then oxidized in the air at 400°C/500°C/600°C for 10 hours. An XRD phase analysis showed that a very high percentage of Fe20 3 was present in the final powder preparation. A conventional processing method was then done to prepare hexagonal BaFe'20'9 pallet shaped samples. Analysis of samples was done on grain size, saturation magnetization, coercive force and remanence. The magnetic properties were measured using approximation method (APM) theory. The high remanence 20000e, 20000e saturation magnetisation and 15000e coercive force of sample derived from millscale shows that this technique used has a high percentage for magnetic properties measurement in the future.